2022
DOI: 10.1111/jnu.12812
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress, social support, and family satisfaction among family members of non‐COVID‐19 critical care patients: A cross‐sectional study

Abstract: Purpose: This study aims to explore the associations among psychological distress, perceived social support, and family satisfaction among family members of non-COVID-19 intensive care unit (ICU) patients during the COVID-19 pandemic. Design:A cross-sectional study. Methods: Family members of patients with at least 48 h in the ICU and without a COVID-19 diagnosis were screened between January and March 2021. For enrolled ICU family members, five questionnaires for perceived stress (Perceived Stress Scale), anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 63 publications
0
13
2
1
Order By: Relevance
“…Our findings were comparable to a recent single‐centre study of 63 family members of non–COVID‐19 critically ill patients, who had a mean FS‐ICU/total of 70.5 (SD, 18.6). 27 In contrast, a recent study from Portugal found an overall family satisfaction of more than 80% during the pandemic. 24 This study was, however, different from our study.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Our findings were comparable to a recent single‐centre study of 63 family members of non–COVID‐19 critically ill patients, who had a mean FS‐ICU/total of 70.5 (SD, 18.6). 27 In contrast, a recent study from Portugal found an overall family satisfaction of more than 80% during the pandemic. 24 This study was, however, different from our study.…”
Section: Discussionmentioning
confidence: 88%
“… 27 Moreover, instrumental social support activities, such as childcare or assistance with daily chores, may have been limited because of social isolation caused by the stage 4 restrictions across Melbourne. 27 Full personal protective equipment donned by HCWs could have masked verbal and nonverbal cues, contributing to lower family satisfaction. 7 , 28 The lack of HCW support due to time constraints 8 could have resulted in insufficient opportunities for families to raise their concerns and/or acquire satisfactory answers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Adams et al, 2017 , Ågård et al, 2019 , Avcı and Ayaz-Alkaya, 2022 , Carlson et al, 2015 , Cohen et al, 1983 , Cribari-Neto and Zeileis, 2010 , Ferrari and Cribari-Neto, 2004 , Fumis et al, 2008 , Haines et al, 2015 , Iverson et al, 2014 , Jo et al, 2019 , Kohi et al, 2016 , Kroenke et al, 2001 , Padilla Fortunatti, 2014 , Padilla-Fortunatti et al, 2022a , Padilla-Fortunatti et al, 2022b , Poblete et al, 2015 , R Core Team, 2021 , Rothen et al, 2010 , Saldivia et al, 2019 , Sherbourne and Stewart, 1991 , Sundararajan et al, 2012 , Tapia et al, 2007 , van Beusekom et al, 2016 , von Elm et al, 2008 , Wall et al, 2007 , Wittenberg et al, 2021 .…”
Section: Uncited Referencesmentioning
confidence: 99%